Industri Kerajinan Perak dalam Analisis Komponen Daya Tarik Wisata (Studi Kasus pada "Studio 76" Kotagede - SETYARINI, Adek Ayuk Nova ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Silver craft of Kotagede is a hereditary culture and still hold its traditional characteristics. Its traditionalism is a unique attractiveness which has made silver craft of Kotagede a vogue until nowadays. There are many foreign visitors who come to Kotagede to learn about the silver craft on their own. Studio 76 Kotagede specifically teach people who interested in the making of silver craft so that in a short period of term its participants are able to make their own silvery jewelry such as ring, earing, and pendant. The purpose of this study is to know the type of products which has become the appeal in Studio 76 Kotagede and to know the component analysis of those products. The data were obtained from literature study, observation, interview and some required references which then were categorized based on the problems that have been analyzed by the researcher. Studio 76 Kotagede has something to see which means that the visitors are able to see the process of making the silver craft directly. It also has something to do since the visitors are able to make their own silver craft by participating in specific courses arranged by the Studio 76. The last is that it has something to buy in which the visitors are able to take the silver craft that they have made in Studio 76 Yogyakarta as souvenirs. The packet of courses of making silver craft as a Tourism Product which available in the Studio 76 are: Short Course, Fullday Course, Weekend Course, and Arranged Course.